Ablation scar in a single pulmonary vein causes proarrhythmic mechanical destabilization in healthy sheep atria. (24th May 2021) - Gottlieb, LA; Vaillant, F; Abell, E; El-Hamrani, D; Naulin, J; Lamy, J; Kachenoura, K; Quesson, B; Coronel, R; Dekker, LRC
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Catharina Hospital, Eindhoven Medtronic (unrestricted research grant) Background: Ablative pulmonary vein isolation (PVI) prevents AF in 60% of AF patients. The absence of an antiarrhythmic effect of PVI is poorly understood. Atrial and PV stretch is proarrhythmic but the mechanical effect of PV ablation scar on AF arrhythmogenesis is unknown. We hypothesize that single ablation scars are potentially proarrhythmic because they create heterogeneous stretch. Purpose: To evaluate the mechanical effect of a purposely incomplete PVI ablation scar on left atrial (LA) electrophysiology. Methods: Functional cardiac MRIs in vivo in sheep (n = 11) before and 3-months after incomplete PVI by radiofrequency in the right PV (RPV) were analyzed with a feature-tracking algorithm to obtain local strain in the LA. The ablated hearts were explanted and perfused with 1:5 blood:Krebs solution in a dual-chamber working-heart set-up. Diagnostic multi-electrode endocardial catheters were positioned in the RPV and left PV (LPV). Premature stimulation was performed in each PV in low (∼12mmHg) and high (∼25mmHg) LA pressure. Twelve control hearts without ablation scar underwent similar ex vivo investigation. Results: The maximum longitudinal strain of the myocardial wall between the RPV and LPV increased from 20.2 ± 6.2% to 33.5 ± 16.0% (before vs. after ablation, respectively; p = 0.032), whereas the maximum radial strain of the LA septum close to the RPV decreased from 45.6 ± 9.7% to 35.8 ± 7.3% (before vs. after ablation, respectively; p = 0.035). Sustained AF (>30s) was more often induced during stimulation in hearts with ablation scar than in control (25.0% and 11.5% of induction attempts (n = 76 and n = 87) in ablated and control hearts, respectively; p = 0.025). In ablated hearts, an increase in LA pressure augmented AF inducibility (12.8% vs. 37.8% of induction attempts (n = 39 vs. n = 37), low vs. high LA pressure, respectively; p = 0.023), whereas this was not the case in control hearts (4.4% vs. 19.0% of induction attempts (n = 45 vs. n = 42), low vs. high LA pressure; p = 0.289). The number of spontaneous premature atrial complexes (PACs) not leading to AF were similar in ablated and control hearts (0 ± 0 vs. 0 ± 2 total PACs within 20ms of refractory period during premature stimulation protocol, respectively; p = 0.411). The diastolic stimulation threshold of RPV was higher in the ablated than in control hearts (90 ± 63 vs. 79 ± 31mA, respectively; p = 0.049). The refractory period was similar in the ablated and control hearts (237 ± 62 vs. 235 ± 55ms, respectively; p = 0.873). Conclusion: Local ablation scar caused regionally disparate bio-mechanical changes in proximity to ablative energy delivery and increased inducibility of sustained AF especially during increased LA stretch. This was associated with decreased tissue excitability without changes in refractoriness. A single incomplete PVI ablation scar therefore is proarrhythmic. Development of ablation lesion sets that homogenize atrial mechanics and electrophysiology may improve AF ablation success.